A tale of two journeys: El camino de Ishtar Yasín and La jaula de oro de Diego Quemada-Diez - Longan Phillips, Shirley (2019)
El camino (Ishtar Yasin, 2008) and La jaula de oro (Diego Quemada-Diez, 2013) are two different journeys in opposite directions: one goes north and the other, south. In El camino, two small brothers travel from Nicaragua to Costa Rica to find their mother. In La jaula de oro, two boys and a girl travel from Guatemala in search of the so-called American dream. Both stories have in common one single hope: life improvement. This article compares the two stories, which are fundamentally about migration in Central America.